DATA ENVELOPMENT ANALYSIS OF FACTORS FOR FOREST INDUSTRY WAGES AND SALARIES LEVELS IN NUTS 2 REGIONS OF BULGARIA (Innovation in Woodworking Industry and Engineering design, 2026)
Determining the economic efficiency of entire enterprises or of certain processes in the use of resources is a topic of constant relevance. Bulgaria's forest industry is a specific sector that provides employment to the population in all regions of the country. So far, many studies have been done on the economic efficiency of the forestry sector in the country. Human resources in the sector, as well as labor costs, were also investigated. In the present study, a methodology is applied that determines the economic efficiency of employment compared to the salaries paid. In this way, the study determines the optimality in the ratio of employment / wages and answers the question to what extent in each of the regions of the country companies have managed to provide productive jobs with good pay.